PENGARUH ASAM HUMAT DAN ABU TKKS PADA MEDIUM SUB SOIL ULTISOL TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Lambok Hariyanto Pangaribuan; Wawan ' '; Erlida ' Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research to know the effect of humic acid, ash of oil palm empty fruits bunch and it’s interaction at medium of sub soil Ultisol and get the best combination to the growth of palm oil (Elaeis guineensis Jacq.) seedling in main nursery. This research was done in a Complete Random Device (CDR) consists of two factors with three replications. The first factor is humic acid which consists of three levels (0, 25 and 50 g/polybag) and the second factor is ash of oil palm empty fruits bunchwhich consists of four levels (0, 25, 50 and 75 g/polybag). Data were analyzed by analysis of variance (ANOVA) andfurthertestedusingDuncan’sNewMultiple RangeTest(DNMRT) atthe significant level of 5%.The parameters observed were the increment of seedling’s height (cm), increment of seedling’s hump diameter (cm), increment of seedling’s leaf (sheet), root volume of seedling (ml),dry weight of seedling (g) and root crown ratio (g). The results of research showed the combination of humic acid and ash of oil palm empty fruits bunch gavesignificant effect toincrement of seedling’s height, seedling’s hump diameter, seedling’s leaf, root volume of seedling. The application 25 g/polybag of humic acid with 25 g/polybag of ash of oil palm empty fruits bunch is the best combination. Giving of humic acidgavesignificant effect to increment of seedling’s hump diameter and seedling’s leaf. Giving of ash of oil palm empty fruits bunchgavesignificant effect to increment of seedling’s height, seedling’s hump diameter, seedling’s leaf, root volume of seedling and dry weight of seedling. Keywords: humic acid, ash of oil palm empty fruits bunch, oil palm seedling.